1997
DOI: 10.1161/01.atv.17.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Vascular Cell Adhesion Molecule-1 Correlates With the Extent of Human Atherosclerosis in Contrast to Circulating Intercellular Adhesion Molecule-1, E-Selectin, P-Selectin, and Thrombomodulin

Abstract: Secondary prevention of atherosclerosis, especially before the onset of symptoms, appears desirable and could be possible with a serum marker detecting atherosclerosis. Circulating, shedded forms of adhesion molecules may serve as such because their expression is upregulated in atherosclerotic plaques. In 52 patients with peripheral arterial vascular disease (Fontaine class IIa, 7 patients; class IIb, 29 patients; and class III, 16 patients), the extent of atherosclerosis was evaluated on the basis of angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
183
2
18

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(215 citation statements)
references
References 32 publications
12
183
2
18
Order By: Relevance
“…As previously mentioned, it is unlikely that fish oil therapy for Ͻ1 year significantly changed the extent of atherosclerosis, which has been shown to correlate to the levels of VCAM-1 in one study. 34 In this study, we found that the levels of sE-selectin were increased after administration of n-3 fatty acids for 6 weeks and then decreased after more prolonged treatment. Although the mechanisms by which these soluble molecules are released into the circulation are not well known, Newman et al 35 demonstrated that membrane-bound E-selectin was cleaved into the soluble form in vitro.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As previously mentioned, it is unlikely that fish oil therapy for Ͻ1 year significantly changed the extent of atherosclerosis, which has been shown to correlate to the levels of VCAM-1 in one study. 34 In this study, we found that the levels of sE-selectin were increased after administration of n-3 fatty acids for 6 weeks and then decreased after more prolonged treatment. Although the mechanisms by which these soluble molecules are released into the circulation are not well known, Newman et al 35 demonstrated that membrane-bound E-selectin was cleaved into the soluble form in vitro.…”
Section: Discussionmentioning
confidence: 51%
“…33 However, it is highly improbable that treatment of dyslipidemia with fish oils could lead to a significant reduction in the extent of atherosclerosis within 12 months based on previous clinical data. 34 In our previous study, levels of sE-selectin but not sICAM-1 were significantly decreased after treatment of hypercholesterolemia with an HMG-CoA reductase inhibitor for 6 months.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, other mechanisms must be active in non-insulin-dependent diabetic patients without complications and these lead to earliest endothelial changes. In this context, circulating concentrations of soluble VCAM-1 but not of other endothelial adhesion molecules, i. e. intercellular adhesion molecule-1, E-selectin and P-selectin and thrombomodulin correlated with the extent and severity of atherosclerosis in humans [10]. …”
Section: Discussionmentioning
confidence: 89%
“…27,34 There are, however, some notable exceptions. 31,35 Soluble ICAM-1, soluble VCAM-1 and atherogenic risk factors Although the available evidence does suggest a relation between sICAM-1, sVCAM-1 and atherosclerosis, the extent of the association is debated and it remains uncertain whether they are independent indicators. 22,36 As Rizzoni and colleagues report, many risk factors for atherosclerosis, including diabetes and hypertension, are generally (though not always) associated with increased levels of sICAM-1 and sVCAM-1.…”
Section: Soluble Icam-1 and Vcam-1 As Markers Of Atherosclerosismentioning
confidence: 99%